Cosmopolitan EU? Minority Rights and the Management of Cultural Diversity - Pace, Cristina Luísa (2018)
The central purpose of this research is to investigate the main progresses in promoting European integration strategies, social cohesion and sense of belonging (both global and European citizenship) within and by the European Union, taking into account the new multicultural realities of our globalized world; promoting a new model of integration which does involve neither homogenization nor hegemonization, allowing for both protection of human rights and the preservation of cultural values. Integration is in fact considered as a key element of the European Union’s migration policy, as well as a crucial element for the future development of European societies, besides the very identity of Europe itself. To this end a comparison is made between the classic and contemporary cosmopolitan theories and the human rights theory, in order to discover if and in which way they may or should complement each other. The idea of cosmopolitanism is questioned and criticized in parallel with the classical Westphalian sovereignty model, which represented and still represents the dominant governance model of international law and relations, notwithstanding the recent rise and development of international global institutions and non-governmental actors, proposing an alternative and new model of “global governance”. I therefore analyze the relationship between two famously conflicting ideologies of human rights: universalism and cultural relativism, in their philosophical and metaethical meaning of the liberal-communitarian debate; in the historical perspective of the post cold-war scenario, which saw the rise and establishment of an international community based on a “common view and scope” and on allegedly “shared values and principles”. The main purpose here is the one of investigating whether or not those values and principles, certified and promoted by the UDHR and other important treaties and declarations since 1948, can be really considered universal and universally shared, besides all cultural differences and relativism. I consider these issues as historically and ideologically related to the actual structure of the international and European system of protection of minorities and cultural diversity, which developed on a parallel although different line. The main intention here is the one of investigating merits and faults of this system, analyzing the new concept and definition of minorities in the European Union context, the European Union competences in this field and the possible mutual cooperation between the EU and other international actors acting for the protection of minority rights. Following OHCHR indications, there is still “no internationally agreed definition as to which groups constitute a minority”, while it is always stressed the fact that the existence of a minority should be recognized as a matter of fact and that any definition must include both objective and subjective aspects (race, ethnicity, language or religion but also identity and sense of belonging). I eventually evaluate different models of integration and European mechanisms of protection of cultural diversity, suggesting a path for a new model of European integration and human rights protection. The role of both states and supranational institutions like the European Union in protecting those rights is considered as essential in this respect.